Pengembangan E-Module Interaktif pada Materi Kingdom Monera Kelas X SMA - Jayanti, Wahyu Ratna; Yeni, Laili Fitri; Titin, Titin (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This research aims to develop an interactive E-Module on Kingdom Monera material. The research method used is R&D (Research & Development) using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The data source for this research is 15 students consisting of class X Science 3 at SMA Negeri 9 Pontianak who were selected using the technique random sampling by lottery. The research instruments used were content validation sheets and student response questionnaires. Validation was carried out by five validators, namely Lecturers in the Biology Education Study Program, Faculty of Teacher Training and Education, Tanjungpura University, and 4 Biology Teachers from SMA Negeri 7 Pontianak, SMA Negeri 9 Pontianak, SMA Negeri 11 Pontianak, and MA Negeri 1 Pontianak, and analyzed using Aiken's V to knowing the validity of the content, as well as the Interclass Correation Coefficient to determine reliability. Validation is carried out by filling out a questionnaire sheet regarding four aspects, namely appropriateness of content, language, presentation and graphics. The ICC reliability results were 0.824 and the Aiken's V validity was 0.93, fulfilling the very good category. Meanwhile, students' responses used three aspects, namely aspects of cognition, affection and conation. In the cognitive aspect, the average was 85.42, the affection aspect was 86.00 and 87.50. From these three aspects, an overall average of 86.31 was obtained in the good category. It can be concluded that the interactive E-Module on Kingdom Monera material is suitable for use in the learning process.